Methodologies and Tools for OSS: Current State of the Practice - Hashmi, Zulqarnain; Shaikh, Siraj; Ikram, Naveed (Electronic Communications of the EASST, 2010)
Over the years, the Open Source Software (OSS) development has matured and strengthened, building on some established methodologies and tools. An understanding of the current state of the practice, however, is still lacking. This paper presents the results of a survey of the OSS developer community with a view to gain insight of peer review, testing and release management practices, along with the current tool sets used for testing, debugging and, build and release management. Such an insight is important to appreciate the obstacles to overcome to introduce certification and more rigour into the development process. It is hoped that the results of this survey will initiate a useful discussion and allow the community to identify further process improvement opportunities for producing better quality software.